Akibat Hukum Pelaksanaan Wasiat yang Tidak Memenuhi Bagian Mutlak Ahli Waris - Tambajong, Helena Benedicta; Lieke Lontoh, Rietha; Mangundap, Annita T.S.F. (UNES Law Review, 2023)
Inheritance granting that violates the restrictions and conditions as well as the legitimate portie of the legitimate heirs can cause problems. To overcome this, it is necessary to study how the regulations of inheritance work with the provisions of the applicable Law, in this case the Civil Law, so that it does not prejudice the rights of others; what is the legal power of a testament; as well as the legal consequences of ittowards the legitimate heirs according to the Civil Code. The research method used was normative juridical research which refers to collecting data through library research then the data was analyzed resulting in conclusions based on deductive thinking method. The resultsindicated that inheritance in the Civil Law is regulated in Book II. The legal power of testaments is stated in Chapter XIII Articles 957-972. The legal consequences arising from a testament that violates the absolute right of the legitimate heirs depend on their actions. If the legitimate heirs do not sue, the testament remains legitimate valid. However, if the legitimate heirs make a claim, then the testament must undergo an inkorting (curtailment) to fulfill the absolute right of the less legitimate heirs.